Musical coexistence of gendhing gati mardawa in the accompaniment of bedhaya sang amurwabumi dance - Raden Mas Surtihadi; Bayu Wijayanto (Pascasarjana Institut Seni Indonesia Surakarta, 2026)
This study discusses the musical coexistence in Gendhing Gati Mardawa as an accompaniment to the Bedhaya Sang AmurwabumiDance, by highlighting how the musical construction of Javanese tradition negotiates with the aesthetic context, history, and cultural representation in the contemporary era. This study uses a qualitative method with a case study approach, the research analysis combines three main perspective lenses: postcolonial, hybridity, and musicology. Through a postcolonial perspective, this study examines how traces of power discourse, palace cosmology, and Javanese cultural narratives are rearticulated through the structure of the gendhing. The hybridity perspective is used to examine the mixture of traditional musical elements, such as the balungan pattern, the accompaniment work, and the relationship of the gendhing structure with the aesthetic needs of palace performances, resulting in a musical form that is not entirely traditional but still maintains its cultural legitimacy. Meanwhile, the musicological perspective provides a foundation for reading the relationship between musical structure, ritualistic function, and the embodied experience of gamelan musicians, musicians, and dancers. The results of this study indicate that Gendhing Gati Mardawa displays a coexistence between the harmony of gamelan instruments and European musical instruments, never in harmony, in the accompaniment to the Bedhaya Sang Amurwabumi Dance. This coexistence not only enriches the aesthetic experience but also offers new insights into how the karawitan tradition transforms through a dialogue between cultural continuity and contemporary artistic demands. This research contributes to the study of dance accompaniment music, demonstrating that musical hybridity should not be understood as deviation, but rather as an adaptive expression that maintains cultural relevance in the context of court performances.